PENERAPAN EDUPING DENGAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Wira Neni Setyaningrum; Khamdun; Siti Masfuah (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
A high level of proficiency in solving problems methodically is a component of critical thinking. By using EDUPING (E-Module based on Mind Mapping) combined with a cooperative learning approach. This research aims to measure the increase in students' critical thinking abilities through thematic learning in class VI of an elementary school. This research uses an experimental design with a pre-experiment and one-group pretest-posttest layout. This research involved 27 participants, all of whom were class VI students at SD N 3 Terban. Because it is a saturated sample, the sample size is proportional to the population. The written exam serves as a research tool. The results were checked with the N-gain test. Based on the test results, the average N-Gain test was obtained at 0.37, which is in the medium category, and the increased test used paired-samples t-test, the sig value (2-tailed) was 0.00 < 0.05, which means Ha is accepted and H0 rejected, which means there is an increase in using EDUPING (E-Module based on Mind Mapping) with a cooperative learning model in electric current material.